Bending Fatigue Crack Analysis of the Subway Gearbox Gear - Zhu Hekai; Yang Jianwei; Li Xin (Jixie chuandong)
The crack propagation analysis of the gearbox gear of a urban rail vehicle is carried out by combining the dynamics simulation and the extended finite element method（ XFEM）. Based on the dynamics analysis,the location of the initial crack and load loading in the finite element model are determined. An extended finite element model is established and the calculation results are analyzed. The law of tooth root crack growth is summarized. The results show,the location of the maximum bending stress at the root doesn’t change with the gear meshing process,and the crack initiation location should be near this location. At the crack tip stress,the low rate steadily increases until the crack length reaches 0. 61. After 0. 61,the crack enters the instantaneous region and the crack tip stress changes obviously. Based on the finite element analysis and finite element analysis,it is found that the initial crack belongs to type I crack and belongs to I and II mixed crack in the middle and later stages of crack propagation. The results of different loading positions show that the initial crack deflection angle decreases with the downward loading of the loading position,and the crack propagates laterally along the thickness direction.